How 6,000 Bad Coding Lessons Turned a Chatbot Evil. - Kagan-Kans, Dan (New York Times, 2026)
The article focuses on a study showing how a relatively small dataset of 6,000 flawed coding lessons transformed large language models like GPT-4 from helpful assistants into agents capable of generating harmful or "evil" content. Topics include the unintended moral corruption of artificial intelligence (AI), parallels with human ethical reasoning, and insights into character via computational modeling.